INFRASTRUCTURAL FINANCING AND INDUSTRIAL SECTOR PERFORMANCE IN NIGERIA - Okwuosa, Galeed Idowu (American Journals Publishing, 2024)
This study was motivated by the need to empirically examine the influence of government infrastructural financing on industrial sector performance in Nigeria. The study disaggregated infrastructural financing by the government according to the Central Bank of Nigeria’s (CBN) statistical bulletin classification which includes Government Financing on Road and Construction (GFRC), Government Financing on Transport and Communication (GFTC), Government Financing on Internal Security (GFIS) and Government Financing on Other Economic Services (GFOES) while industrial sector performance was measured by Industrial Sector Output (ISO) contribution to national output. Both descriptive and inferential statistics was used to analyzed data obtained from the CBN’s statistical bulletin between 1994 and 2022. The inferential statistics helped us to determine the relationship between the implicated variables through the application of the Autoregressive Distributive Lag (ARDL) and its associated bond test given the fractional integration recorded with our stationarity test while Granger causality test was used to determine the causal relationship between the implicated variables. From our findings, GFRC and GFOES had positive influence on ISO and were insignificant while GFTC and GFIS were negative and insignificantly related with ISO. The study further reported absence of a long run relationship between government infrastructural financing and industrial sector performance while a unidirectional relationship was recorded between GFRC and industrial sector performance and bidirectional relationship between GFIS and industrial sector performance. The study recommends the need to enhance the quality of GFRC and GFOES and other aspect of infrastructure to ensure their optimum performance through constant monitoring and budget evaluations.
Keywords: Infrastructural Financing, Industrial Sector Performance, Keynesian Economist, Resource based View, and Wagner’s Law.